The Multimodal Indonesian Flipbook E-Module for Vocational High School Students: Spotlighting the Usefulness - Mhd Virzha Nafandri Utama; Isah Cahyani; Khaerudin Kurniawan (AL-ISHLAH: Jurnal Pendidikan, 2023)
Since the learning process was carried out for approximately two years due to the COVID-19 pandemic, teachers and students have experienced problems in learning, especially in writing anecdotes, such as lack of student enthusiasm, decreased learning quality, students feeling bored, and so on. This study aims to describe the use of multimodal-based flipbook e-modules in Vocational High Schools. The research instrument was a teacher interview guide, a list of student needs questions, and a list of student response questions. The type of research used is research and development (RD) using the ADDIE method. Based on the test results, it is known that the average score of students' assessment of all aspects of the assessment is 4.44 which is included in the very good category. The highest assessment aspect is in the presentation of material, with an average of 4.75. The aspect of assessment with the lowest average is the aspect of readability, with an average of 4.39. The final product results are based on needs analysis, the results of the E-Module validation assessment, and the test results, namely the E-Module product with the Flipbook technique as a teaching material that is developed very interesting and learning is not boring.